2010
DOI: 10.1016/j.contraception.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a combined oral contraceptive in obese and normal-weight women

Abstract: Background This study was conducted to compare oral contraceptive (OC) pharmacokinetics (PK) in normal weight (BMI 19.0-24.9) and obese (BMI 30.0-39.9) women. Study Design During the third week of the third cycle of OC use, we admitted 15 normal weight and 15 obese women for collection of 12 venous specimens over 24 h. Using RIA techniques, we measured levels of ethinyl estradiol (EE) and levonorgestrel (LNG). During the same cycle, women underwent twice-weekly sonography to assess ovarian follicular develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
76
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 13 publications
13
76
1
10
Order By: Relevance
“…The traditional model for mixed inhibition involves one inhibitor binding site that is removed from the active site. This site may have its conformation altered by the presence or absence of substrate at the active site, such that the affinity for (Westhoff et al, 2010). b In pregnant women (Piwowarska et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional model for mixed inhibition involves one inhibitor binding site that is removed from the active site. This site may have its conformation altered by the presence or absence of substrate at the active site, such that the affinity for (Westhoff et al, 2010). b In pregnant women (Piwowarska et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…21 Another study demonstrated lower serum concentrations of both EE and LNG in obese women, but trough levels were not significantly different. 22 The implication of these findings on the contraceptive efficacy of oral contraceptives may be small or negligible, as the minimum concentrations of LNG were sufficient to suppress ovulation. Again, there was evidence of more follicular activity in obese patients.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A body of literature has emerged focusing on the unique metabolic changes observed in obesity, pharmacokinetic alterations, and their effect on contraceptive efficacy. [20][21][22]24,25 Studies overall have been conflicting, but concern exists about increased rates of failure of hormonal contraceptives in this subset of women. The etiology of this finding is not well understood but is thought to be a result of alterations in the pharmacokinetics and metabolism of steroid hormone contraceptives.…”
Section: Consequences Of Obesity Regarding Fertilitymentioning
confidence: 99%
See 2 more Smart Citations